Iran’s Political Problems from the Viewpoint of Female Travelers in the Nasseri Era - Mohiedin Khalkhali, Seyed (2020)
The objective of this study was to analize the Iran’s Political Problems from the Viewpoint of Female Travelers in the Nasseri Era. Refering to the methodology: this research has been done by descriptive method and by studying written and historical works. Researchers have extracted material by examining historical books, articles and writings. In this study, we have tried to collect and sort out the problems of passengers. Results show that during Qajar Era, due to the strategic position of Iran and the Persian Gulf, this region was of particular interest to the superior international powers; therefore, travelers, statesmen, ambassadors, and merchants from many different European and non-European countries traveled to Iran. In these foreign delegations and political groups, there were also female figures, including Lady Sheil, Jane Dieulafoy, Gertrude Bell, Madame Wolfson, Isabella Bird Bishop and Carla Serena. Some of these women came to Iran as members of political delegations and some for tourism or economic purposes. Regarding their status and position, they provided Qajar officials with reports in which they addressed Iran's political problems, such as the government's failure in managing public health and justice, dealing with insecurity, widespread economic corruption among statesmen and other authorities of Qajar government, oppressions, and the like. According to the results, it can be said that most of these problems are related to the internal structure of Iran as well as the culture of Iranians and some customs of that time.